Limits on the anomalous ZZγ and Zγγ couplings in pp̄ collisions at √s = 1.8 TeV - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Álvarez, G; Alves, G; et al. (1995)
We performed a direct search for the anomalous ZZγ and Zγγ couplings by studying pp̄ → ℓℓγ + X (ℓ = e, μ) events at √s = 1.8 TeV with the D0 detector at the Fermilab Tevatron Collider. A fit to the transverse energy spectrum of the photon in the signal events, based on the data set corresponding to an integrated luminosity of 14.3 pb-1 (13.7 pb-1) for the electron (muon) channel, yields the following 95% confidence level limits on the anomalous CP-conserving ZZγ couplings: |h30Z| < 1.8 (h40Z = 0) and |h30Z| < 0.5 (h30Z = 0), for a form-factor scale A = 500 GeV. Limits for the Zγγ couplings and CP-violating couplings are also discussed.